An appropriate ammonium: nitrate ratio promotes the growth of centipedegrass: insight from physiological and micromorphological analyses - Hao, Dong-Li; Zhou, Jin-Yan; Li, Ling; Qu, Jia; Li, Xiao-Hui; Chen, Rong-Rong; Kong, Wei-Yi; Li, Dan-Dan; Li, Jian-Jian; Guo, Hai-Lin; Liu, Jian-Xiu; Zong, Jun-Qin; et al. (Frontiers in Plant Science, 2023)
Reasonable nitrogen fertilizer application is an important strategy to maintain optimal growth of grasslands, thereby enabling them to better fulfil their ecological functions while reducing environmental pollution caused by high nitrogen fertilizer production and application. Optimizing the ammonium (NH4 + ):nitrate (NO3 -) ratio is a common approach for growth promotion in crops and vegetables, but research on this topic in grass plants has not received sufficient attention. Centipedegrass, which is widely used in landscaping and ecological protection, was used as the experimental material. Different NH4 + :NO3 -ratios (0: 100, 25:75, 50:50, 75:25, 100:0) were used as the experimental treatments under hydroponic conditions. By monitoring the physiological and morphological changes under each treatment, the appropriate NH4 + :NO3 -ratio for growth and its underlying mechanism were determined. As the proportion of ammonium increased, the growth showed a "bell-shaped" response, with the maximum biomass and total carbon and nitrogen accumulation achieved with the NH4 + :NO3 -ratio of 50:50 treatment. As a gateway for nitrogen input, the roots treated with an NH4 + :NO3 -ratio of 50:50 exhibited the highest ammonium and nitrate uptake rate, which may be related to the maximum total root length, root surface area, average root diameter, root volume, and largest root xylem vessel. As a gateway for carbon input, leaves treated with an NH4 + :NO3 - ratio of 50:50 exhibited the highest stomatal aperture, stomatal conductance, photosynthetic rate, transpiration rate, and photosynthetic products. The NH4 + :NO3 - ratio of 50:50 treatment had the largest stem xylem vessel area. This structure and force caused by transpiration may synergistically facilitate root-to-shoot nutrient translocation. Notably, the change in stomatal opening occurred in the early stage (4 hours) of the NH4 + :NO3 -ratio treatments, indicating that stomates are structures that are involved in the response to changes in the root NH4 + :NO3 -ratio. In summary, we recommend 50:50 as the appropriate NH4 + :NO3 -ratio for the growth of centipedegrass, which not only improves the nitrogen use efficiency but also enhances the carbon sequestration capacity.